Inhibition of lymphocyte trafficking shields the brain against deleterious neuroinflammation after stroke - Liesz, Arthur; Zhou, Wei; Mracskó, Eva; Karcher-Bausch, Simone; Bauer, Henrike; Schwarting, Sönke; Sun, Li; Bruder, Dunja; Stegemann, Sabine; Cerwenka, Adelheid; Sommer, Clemens; Dalpke, Alexander; et al. (Brain, 2011)
T lymphocytes are increasingly recognized as key modulators of detrimental inflammatory cascades in acute ischaemic stroke, but the potential of T cell-targeted therapy in brain ischaemia is largely unexplored. Here, we characterize the effect of inhibiting leukocyte very late antigen-4 and endothelial vascular cell adhesion molecule-1-mediated brain invasion—currently the most effective strategy in primary neuroinflammatory brain disease in murine ischaemic stroke models. Very late antigen-4 blockade by monoclonal antibodies improved outcome in models of moderate stroke lesions by inhibiting cerebral leukocyte invasion and neurotoxic cytokine production without increasing the susceptibility to bacterial infections. Gene silencing of the endothelial very late antigen-4 counterpart vascular cell adhesion molecule-1 by in vivo small interfering RNA injection resulted in an equally potent reduction of infarct volume and post-ischaemic neuroinflammation. Furthermore, very late antigen-4-inhibition effectively reduced the post-ischaemic vascular cell adhesion molecule-1 upregulation, suggesting an additional cross-signalling between invading leukocytes and the cerebral endothelium. Dissecting the specific impact of leukocyte subpopulations showed that invading T cells, via their humoral secretion (interferon-γ) and immediate cytotoxic mechanisms (perforin), were the principal pathways for delayed post-ischaemic tissue injury. Thus, targeting T lymphocyte-migration represents a promising therapeutic approach for ischaemic stroke.
Gesehen am 13.09.2022